Why men watch soap peras a study on the uses and gratifications derived by male college students from soap opera viewing - Tan, Vicente R. (Iloilo City UP Visayas, 2006)
"This study examines the viewing patterns of male dormitory residents towards the Taiwanese soap opera Meteor Garden through the uses and gratifications theory. Gratification has been categorized as entertainment, social integration, personal identity and passing time. The social and psychological origins of gratification are founded on four psychological theories of McGuire (1985) cited by Conway and Rubin (1991), namely hermeneutic & attributional, stimulation & sensation seeking theory, tension reduction and anxiety, and parasocial and attraction theory. Majority of the male dormers claimed to be watching soap operas. These soap opera viewers were 16 and 17-year-old freshmen enrolled in natural and physical sciences courses. Boredom, stress, anxiety, need to participate in friends' conversations and classroom discussions, admiration and fanaticism, lack of other activities to engage in and need to relax are among the most common indicators of the social and psychological motives expounded by the interviewees."
Keywords: Men -- Psychology; Meteor garden soap opera series